Lateral annular systolic excursion ratio: A novel measurement of right ventricular systolic function by two-dimensional echocardiography - Stock, Jonathan D.; Rothstein, Eric S.; Friedman, Scott E.; Gemignani, Anthony S.; Costa, Salvatore P.; Milbridge, Andrew J.; Zhang, Rui; Taub, Cynthia C.; O'Rourke, Daniel J.; Palac, Robert T. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Accurate assessment of right ventricular (RV) systolic function has prognostic and therapeutic implications in many disease states. Echocardiography remains the most frequently deployed imaging modality for this purpose, but estimation of RV systolic function remains challenging. The purpose of this study was to evaluate the diagnostic performance of a novel measurement of RV systolic function called lateral annular systolic excursion ratio (LASER), which is the fractional shortening of the lateral tricuspid annulus to apex distance, compared to right ventricular ejection fraction (RVEF) derived by cardiac magnetic resonance imaging (CMR). Methods: A retrospective cohort of 78 consecutive patients who underwent clinically indicated CMR and transthoracic echocardiography within 30 days were identified from a database. Parameters of RV function measured included: tricuspid annular plane systolic excursion (TAPSE) by M-mode, tissue Doppler S’, fractional area change (FAC) and LASER. These measurements were compared to RVEF derived by CMR using Pearson’s correlation coefficients and receiver operating characteristic curves. Results: LASER was measurable in 75 (96%) of patients within the cohort. Right ventricular systolic dysfunction, by CMR measurement, was present in 37% (n = 29) of the population. LASER has moderate positive correlation with RVEF (r = 0.54) which was similar to FAC (r = 0.56), S’ (r = 0.49) and TAPSE (r = 0.37). Receiver operating characteristic curves demonstrated that LASER (AUC = 0.865) outperformed fractional area change (AUC = 0.767), tissue Doppler S’ (AUC = 0.744) and TAPSE (AUC = 0.645). A cohort derived dichotomous cutoff of 0.2 for LASER was shown to provide optimal diagnostic characteristics (sensitivity of 75%, specificity of 87% and accuracy of 83%) for identifying abnormal RV function. LASER had the highest sensitivity, accuracy, positive and negative predictive values among the parameters studied in the cohort. Conclusions: Within the study cohort, LASER was shown to have moderate positive correlation with RVEF derived by CMR and more favorable diagnostic performance for detecting RV systolic dysfunction compared to conventional echocardiographic parameters while being simple to obtain and less dependent on image quality than FAC and emerging techniques.